Study on efficacy and performance of Artemisia argyi extracts - ZHANG Wan-ping; ZHANG Zhi-yuan; ZHANG Dong-mei; ZHANG Qian-jie; JIANG Wen (Shipin yu jixie)
Objective: By analyzing bacteriostasis and efficacy, the possibility of Artemisia argyi extract to be a plant extract preservative is clarified. It provides a message for the development of natural non-irritating plant extract preservative. Methods: Water and ethanol extracts of A. argyi were prepared. The content of its main active components was determined. Its inhibitory effect and stability on Escherichia coli and Staphylococcus aureus were analyzed. Antioxidant activity, ultraviolet absorption capacity and security were also discussed. Results: The ethanol extract of A. argyi had a significant inhibitory effect on the two kinds of bacteria, which was related to the content of active components to some extent. Temperature and UV irradiation had no significant effect on antibacterial activity, while pH had a greater effect on antibacterial activity. At the concentration of 0.96 mg/mL, ethanol extract of A. argyi leaves could eliminate 98% of DPPH and ABTS free radicals, and more than 50% of superoxide anion and hydroxyl free radicals. When the concentration was 0.5 mg/mL, the two extracts had good ultraviolet absorption capacity. The HET-CAM test showed that the extract of A. argyi had high security at the concentration of 62.5 mg/mL. Conclusion: The ethanol extract of A. argyi has good and stable bacteriostatic effect, certain antioxidant activity, ultraviolet absorption performance and security.